2016
DOI: 10.18632/oncotarget.7049
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants in association with reducing risk of oral cancer occurrence: a nationwide population-based cohort and nested case-control studies

Abstract: ObjectivesSeveral studies suggested that antidepressant use may increase or decrease the risk of cancer occurrence, depending on specific cancer types. The possible carcinogenic effect of antidepressants has received substantial attention; however, evidence remains inconclusive. Here we investigated associations between the use of antidepressants and occurrences of oral cancer (OC).MethodsTwo million samples were randomly collected from the National Health Insurance Research Database in Taiwan, which covers 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Hence, the subgroup who exceeds 80 years old was excluded in this study. In addition, the reason that we set antidepressant users who had been prescribed at least 30 days is because depressive symptoms get improved within this period of time [36] and this criterion is widely accepted in other studies [4042]. …”
Section: Discussionmentioning
confidence: 99%
“…Hence, the subgroup who exceeds 80 years old was excluded in this study. In addition, the reason that we set antidepressant users who had been prescribed at least 30 days is because depressive symptoms get improved within this period of time [36] and this criterion is widely accepted in other studies [4042]. …”
Section: Discussionmentioning
confidence: 99%
“…This is an outcome of neurological changes in the Central Nervous System (CNS). However, the key agents with a pivotal role in learning and memory processes are ADA, MAO‐A, AChE, and BuChE enzymes (Benamar et al, ; Chung et al, ). Recent studies have also shown that mixture of heavy metals and organic pollutants, are capable of enhancing the activities of ADA, MAO‐A, AChE, and BuChE (Akintunde & Oboh, ; Miguel et al, ; Sánchez‐Santed et al, ) thus, causing memory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegeneration encompassing cognitive impairment is a metabolic disorder characterized by high activities of mono‐amine oxidase‐A (MAO‐A), adenosine deaminase (ADA), acetyl cholinesterase (AChE), butrylcholinesterase (BuChE) and low levels of brain nucleotides (Benamar et al, ; Chung et al, ; Osman & Osman, ). This involves the progressive loss of structures or functions of neurons, ranging from molecular to systemic (Estrada‐Sánchez, Mejía‐Toiber, & Massieu, ), amyotrophic lateral sclerosis, Parkinson's, Alzheimer's, and Huntington's diseases (Caccamo, Currò, Condello, Ferlazzo, & Ientile, ; De Vos, Grierson, Ackerley, & Miller, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, in a study, where antidepressant treatment generated modest symptom reductions, antidepressants did not improve symptoms more than placebo in 2 heart failure trials [37]. Moreover, in patients with heart failure depressive symptoms, not antidepressant therapy predicted event-free survival but depressive patients without antidepressants had a 4.1 times higher risk of death and hospitalization than non-depressed patients on antidepressant treatment [38]. …”
Section: In Patients With Cardiovascular Disorders Use Serotonin Reupmentioning
confidence: 99%